Pendampingan Santripreneur, Pesantrenpreneur dan Sosiopreneur di Koperasi Syariah IAI Tarbiyatut Tholabah - Sifwatir Rif'ah; Ahmad Badrut Tamam (PARTISIPATORY, 2025)
One Pesantren One Product (OPOP) is one of the flagship programs of the West Java Provincial Government in order to build pesantren independence. This research is an economic empowerment of the people during the COVID-19 pandemic using the Participatory Action Research (PAR) method with the synergy of santripreneur, pesantrenpreneur and sociopreneur at Tarbiyatut Tholabah Islamic Boarding School (TABAH) through the OPOP program. Collecting data by interview, documentation, observation, Focus Group Discussion (FGD) and action. The results of the study indicate that the implementation of community economic empowerment in the TABAH Islamic Boarding School is by (1) providing entrepreneurship assistance to produce superior products; (2) reactivate the Berlian Syariah cooperative by synergizing between pesantren, santri, and alumni or the surrounding community; (3) obtain assistance and training facilities from government programs through OPOP; (4) has superior products of pesantren with the brand of “Wulung Samudra” consisting of batik, processed sea products and “aitabah” bottled water; (5) the process of legality of superior products of Islamic boarding schools.